Isolation from the Sorghum bicolor Mycorrhizosphere of a Bacterium Compatible with Arbuscular Mycorrhiza Development and Antagonistic towards Soilborne Fungal Pathogens - Budi, S. W. (American Society for Microbiology, 1999)
A gram-positive bacterium with antagonistic activity towards soilborne fungal pathogens has been isolated from the mycorrhizosphere of Sorghum bicolor inoculated with Glomus mosseae. It has been identified as Paenibacillus sp. strain B2 based on its analytical profile index and on 16S ribosomal DNA analysis. Besides having antagonistic activity, this bacterium stimulates mycorrhization.